2018
DOI: 10.1080/14767058.2018.1519536
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of birth weight small for gestational age with and without preeclampsia by angiogenic markers: an Odense Child Cohort study

Abstract: The sFlt-1/PlGF ratio is a potential predictor of SGA in population-based screening, particularly when preeclampsia is also present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Biomarker measurements of placental functioning-related substances have had significant development in the last three decades. Many of these compounds are also involved with antenatal detection of chromosomal anomalies, or preeclampsia, such as PAPP-A, AFP, PlGF, or sFLt-1 [41] (Table 2). Studies from the mid 1980s have evaluated the human placental lactogen (hPL), when it demonstrated a diagnostic odds ratio (DOR) of 4.78 (95% CI 3.21–7.13), whereas more recent data focus on angiogenic biomarkers [44].…”
Section: When and How We Should Screen For Fetal Growth Restriction?mentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarker measurements of placental functioning-related substances have had significant development in the last three decades. Many of these compounds are also involved with antenatal detection of chromosomal anomalies, or preeclampsia, such as PAPP-A, AFP, PlGF, or sFLt-1 [41] (Table 2). Studies from the mid 1980s have evaluated the human placental lactogen (hPL), when it demonstrated a diagnostic odds ratio (DOR) of 4.78 (95% CI 3.21–7.13), whereas more recent data focus on angiogenic biomarkers [44].…”
Section: When and How We Should Screen For Fetal Growth Restriction?mentioning
confidence: 99%
“…PlGF has consistently lower levels in SGA pregnancies, in 2 nd and 3 rd trimesters [8284], especially for BW < 5 th or <10 th centiles. For higher sFlt-1/PlGF ratios, there is better AUC for preeclampsia-associated SGA [40, 41]. These findings point in the direction of angiogenesis-mediated pathophysiology of SGA, especially when there are Doppler abnormal parameters [37].…”
Section: When and How We Should Screen For Fetal Growth Restriction?mentioning
confidence: 99%
“…B, Blood samples were categorized into 3 groups based on gestational age at collection: on or before gw 16, on or before gw 24, and after gw 24. The median gestational age at the time of collection was gw 14 (IQR, 12,15) for the first group, gw 22 (IQR, 20,24) for the second group, and gw 29 (IQR, 28,30)…”
Section: Nonstandard Abbreviations and Acronymsmentioning
confidence: 99%
“…The sFlt-1/PlGF ratio is inversely correlated with BW [ 78 , 79 ] and a high ratio is present in pregnancies complicated by FGR [ 80 ]. Furthermore, although the sFlt-1/PlGF ratio is elevated regardless of the gestation at which FGR is diagnosed, early-onset FGR is associated with higher ratios compared with late-onset FGR, suggesting a possible lesser degree of placental dysfunction in the latter group [ 78 , 81 ].…”
Section: Angiogenic Factorsmentioning
confidence: 99%